Molecular mechanism of Activin receptor inhibition by DLK1 - Daniel Antfolk; Qianqian Ming; Anna Manturova; Erich J. Goebel; Thomas B. Thompson; Vincent C. Luca (Nature Communications)
Abstract Delta-like non-canonical Notch ligand 1 (DLK1) influences myogenesis, adipogenesis, and other aspects of human development through a process that is largely attributed to the downregulation of Notch signaling. Here, we show that DLK1 does not bind to Notch receptors or affect ligand-mediated Notch activation, but instead engages the TGF-β superfamily member Activin receptor type 2B (ACVR2B). The crystal structure of the DLK1-ACVR2B complex reveals that DLK1 mimics the binding mode of canonical TGF-β ligands to compete for access to ACVR2B. In functional assays, DLK1 antagonizes Myostatin-ACVR2B signaling to promote myoblast differentiation, rationalizing a mechanism for the role of DLK1 in muscle development and regeneration. Crosstalk between Notch and TGF-β is mediated by interactions between the transcriptional regulators SMAD2/3 and the Notch intracellular domain (NICD), and DLK1 inhibits SMAD2/3-NICD colocalization. These findings indicate that DLK1 acts directly on ACVR2B to inhibit signaling, whereas the observed effects on Notch may be an indirect result of DLK1 interference with NICD-SMAD complex formation.